Synthesizer concepts for FMCW based locatable wireless sensor nodes - Ußmüller, Thomas; Jung, Melanie; Weigel, Robert (Wireless Sensing, Local Positioning, and RFID, 2009. IMWS 2009. IEEE MTT-S International Microwave Workshop, 2009)
Local positioning systems significantly enhance the value of wireless sensor networks (WSN). This paper first motivates the use of WSN with exemplary application scenarios. Afterwards it shortly addresses the basics of frequency modulated continuous wave (FMCW) systems. Several common synthesizer concepts for FMCW radars are shown. The paper focuses on a novel integrated synthesizer for localization using frequency modulated continuous wave (FMCW) radar. The synthesizer is based on a fractional-n phase-locked loop (PLL) architecture. All components of the PLL are carefully designed with respect to their performance and power consumption. The complete synthesizer was manufactured in a 0.18 mum SiGe BiCMOS process from IBM, and it draws only 39 mA from the supply. It achieves a phase noise better than -113 dBc/Hz and has a silicon area of 1.15 mm2. Due to its high integration level and its optimized design, the synthesizer achieves low power consumption and low phase noise that makes it suitable for precise localization in mobile sensor nodes. Localization measurements in indoor environments with multipath propagation showed mean distance errors about 13 cm.
elib2cris::1512001600,ussmueller2009d
Keywords: BiCMOS integrated circuits; CW radar; FW radar; frequency synthesizers; phase locked loops; radio direction-finding